Development for soft actuator with multilayer structure and its application - Kang, Gyeongji; Song, Kahye (Nature Publishing Group, 2026)
Most actuators require considerable degrees of freedom to perform tasks effectively, which often leads to larger size and reduced portability. As an alternative, soft actuators have been introduced, offering compact form, high maneuverability, and multiple modes of motion. In this study, a Hydraulically Amplified Self-Healing Electrostatics (HASEL) actuator was configured in a layered structure to achieve practical usability and efficient movement. The actuator operates through hydraulic pressure and volumetric expansion generated under high voltage. It was fabricated in a simple rectangular design, and a new type of soft actuator was realized by stacking single units to amplify angular displacement and output force. Precise control is not required, since the gripper’s performance can be tuned by adjusting the number and arrangement of layers. The system can also be adapted for different applications by producing and combining various supporting frames. This paper presents two types of soft grippers based on the layered HASEL actuator, which are expected to be useful in fields such as smart farming systems that demand both adaptability and mobility.